The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1155/2013/141427
|View full text |Cite
|
Sign up to set email alerts
|

Characterization andIn VivoBiological Performance of Biosilicate

Abstract: After an introduction showing the growing interest in glasses and glass-ceramics as biomaterials used for bone healing, we describe a new biomaterial named Biosilicate. Biosilicate is the designation of a group of fully crystallized glass-ceramics of the Na2O-CaO-SiO2-P2O5 system. Several in vitro tests have shown that Biosilicate is a very active biomaterial and that the HCA layer is formed in less than 24 hours of exposure to “simulated body fluid” (SBF) solution. Also, in vitro studies with osteoblastic cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 26 publications
5
41
0
5
Order By: Relevance
“…[14][15][16][17][18] In particular, the use of a new glass-ceramic powder called Biosilicate has been proposed as a therapeutic agent for enamel and dentin regeneration because of the faster deposition of a hydroxyapatite layer where the product is applied. 6,18,19 Biosilicate particles appear to react rapidly with surrounding tissue inside the dentin microchannels 18 resulting in an effective clinical reduction in sensitivity by promoting the occlusion of dentin tubules. 20 When used immediately after bleaching treatment, Biosilicate can reduce or even prevent the demineralization effect of bleaching products and prevent the exposure of dentin tubules.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] In particular, the use of a new glass-ceramic powder called Biosilicate has been proposed as a therapeutic agent for enamel and dentin regeneration because of the faster deposition of a hydroxyapatite layer where the product is applied. 6,18,19 Biosilicate particles appear to react rapidly with surrounding tissue inside the dentin microchannels 18 resulting in an effective clinical reduction in sensitivity by promoting the occlusion of dentin tubules. 20 When used immediately after bleaching treatment, Biosilicate can reduce or even prevent the demineralization effect of bleaching products and prevent the exposure of dentin tubules.…”
Section: Introductionmentioning
confidence: 99%
“…Renno and Vivan suggested that for satisfactory biological interaction to occur, bone replacement graft materials must not only be biocompatible but must also present a high bioactive level resulting in over 50% of living tissue (new bone) being attached to a material surface. This attachment is established through the formation of a layer of biologically active hydroxycarbonate apatite at the material/tissue interface, quite similar to bone tissue apatite.…”
Section: Discussionmentioning
confidence: 99%
“…It should be kept in mind that, while, this holds true for crystallization of typical bioactive glasses, glass-ceramic with tailored crystal composition, size and density can be produced with bioactivity similar to Bioglass ®. Biosilicate is one such material showing promising results both in-vitro and in-vivo [13]. As of today, 3D scaffold obtained via thermal bonding [14][15] and polymer foam replication [16][17][18] can be mainly classified as glass-ceramic.…”
Section: Introductionmentioning
confidence: 99%